Women in Sustainable Development through Management of Wasteland, Forests and Environment - Das, D.C.; Nityanand, D.V. (Journal of Soil and Water Conservation, 2022)
In the socio-economic context sustainability needs to beprecisely clarified considering the target group and the designated level of growth. Tins will also determine the inter-inediary stage of redevelopment of a degraded area and associated natural resources. To this end women's concern for survival, sustenance, development and growth of their families is very important. Their desire for a stable environment or natural resources base that would assure the continuity in the supply of household goods should be an improtant basis for formulating a plan for redevelopment of the degraded area and the eco system. The scenario in rural India reveals complexity due to inadequate attention to the links between the socio economic compulsion, particularly those of women, and the conservation and redevelopment programme. The analysis of existing potential of employment generation under sub sectors of agriculture along with the necessity for a faster rate of increase in the production of fodder, fuel and raw material needed for the communities gives a definite direction. It indicates that other primary . production systems than cultivation coupled with household/small scale enterprises which will be based on biomass produced locally, could offer . sustainability alongwith secured livelihood and prosperity to the com- munities. Since nearly 50 per cent of the work force are women and the stability of the household and their well being depend on them the programme should specifically incorporate their aspirations and needs in all aspects of soil and Water Conservation and afforestation. Because their are the two areas which could translate this into action as has been already experienced at a number project areas.